Impact on railway infrastructure of wayside energy storage systems for regenerative braking management: a case study on a real Italian railway infrastructure. Issue 3 (1st September 2019) - Alfieri, Luisa; Battistelli, Luigi; Pagano, Mario
Abstract : Today, in the railway sector there is considerable interest in studying the best ways of exploiting train braking energy, in order to achieve a reduction in energy costs and better stabilisation of grid voltage. Among the various on‐board or wayside measures proposed, one of the most promising solutions is based on using wayside energy storage systems (WESSs). A WESS is a storage installation which can be integrated into mass transit systems in urban areas as well as into long‐distance railway lines. It can operate as a smart storage system able to provide relevant benefits in terms of recovering surplus regeneration braking energy, voltage stabilisation, reduction of peak power demand. For these purposes, an effective and flexible simulator is essential to provide all the elements needed to focus and compare feasible configurations and operations. This study examines the problem of introducing the WESS technology in real railway infrastructure. It proposes a method based on a simulator of the WESS system integrated into the infrastructure and carries out the results of dynamic simulations referring to real operating data of the system and vehicles. The results highlight the performance of the WESS in terms of energy and power exchange, also discussing economic aspects.